2016
DOI: 10.1177/0022034516656135
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine Nanocapsule Drug Delivery Approach to the Resin-Dentin Interface

Abstract: In this study, we are introducing a new drug-delivery approach to demineralized dentin substrates through microsized dentinal tubules in the form of drug-loaded nanocapsules. Chlorhexidine (CHX) is widely used in adhesive dentistry due to its nonspecific matrix metalloproteinase inhibitory effect and antibacterial activities. Poly(ε-caprolactone) nanocapsules (nano-PCL) loaded with CHX were fabricated by interfacial polymer deposition at PCL/CHX ratios of 125:10, 125:25, and 125:50. Unloaded nanocapsules (blan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 33 publications
(42 reference statements)
0
41
0
Order By: Relevance
“…23,24 Incorporating NCs into the primer and adhesive did not compromise the immediate bond strength, as has been observed in previous studies, 7,9 indicating the reliable distribution of NCs in the hybrid layer. 6,9 Previous studies that tested commercial and experimental adhesives showed similar bond strength results. 25,26 Storage in water satisfactorily mimics clinical restoration degradation 23,27 since it infiltrates, promotes the swelling of and reduces the forces between polymer chains, 10 causing a decrease in the mechanical properties, the elution of monomers and a consequent weakening of the bond.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…23,24 Incorporating NCs into the primer and adhesive did not compromise the immediate bond strength, as has been observed in previous studies, 7,9 indicating the reliable distribution of NCs in the hybrid layer. 6,9 Previous studies that tested commercial and experimental adhesives showed similar bond strength results. 25,26 Storage in water satisfactorily mimics clinical restoration degradation 23,27 since it infiltrates, promotes the swelling of and reduces the forces between polymer chains, 10 causing a decrease in the mechanical properties, the elution of monomers and a consequent weakening of the bond.…”
Section: Discussionmentioning
confidence: 74%
“…9 The chemical affinity between the polymer of the NCs and the monomers of the adhesive system leads to reliable physicochemical properties. 6,7,8,9 The diffusion of nanocapsules in the hybrid layer did not result in a decrease in the immediate bond strength. 7,9 Nonetheless, the influence of the nanocapsules on the long-term bond strength has not yet been elucidated.…”
mentioning
confidence: 93%
See 3 more Smart Citations